PELATIHAN PEMBUATAN NUGGET IKAN BAGI KADER PKK DESA KEBUMEN, KECAMATAN BATURRADEN - Sesilia Rani Samudra; Maria Dyah Nur Meinita; Hendrayana Hendrayana (Universitas Mataram, 2023)
Kebumen Village is a village in Baturraden District, Banyumas Regency, Central Java. The average head of family in this village is a laborer, so the family's economy was affected during the Covid-19 pandemic. So far, many residents in Kebumen Village do not yet have the skills or expertise that can become capital for entrepreneurship. However, the obstacles experienced were that there were no facilitators who provided business skills during the pandemic and there was no budget from village funds. Much of the village budget has been absorbed for the handling of Covid-19. The purpose of this activity is to provide business skills assistance for Kebumen Village PKK Cadres through training activities in making fish nuggets. Community service activities in Kebumen Village as an effort to improve the community's economy during the Covid-19 pandemic. The method of implementing the activity is Participatory Rural Appraisal (PRA), namely by directly practicing making fish nuggets, starting from mincing the meat, mixing the ingredients to make the nugget dough, steaming, cutting the dough, coating the dough with panir flour, to frying the nuggets ready to eat. In addition, participants were also asked to fill out a questionnaire regarding this community service activity. The results of the training activities are increasing the knowledge and skills of PKK cadres in processing modern fish products, as well as generating creative ideas to create business opportunities that are useful for increasing family income during the Covid-19 pandemic. Based on the data from the questionnaire results, it was found that all training participants benefited from the fish nugget making training. The training provided by the community service team to PKK Cadres in Kebumen Village, Baturraden District was considered very useful in increasing knowledge in processing freshwater fish into modern snacks that are worth selling. Participants were very enthusiastic in participating in the entire series of fish nugget making training activities and revealed that this activity could be an idea for doing business in the post-Covid-19 pandemic.